2020
DOI: 10.1002/brb3.1665
|View full text |Cite
|
Sign up to set email alerts
|

Neuro‐Sjögren: Uncommon or underestimated problem?

Abstract: Objectives Sjögren's syndrome (SS) is a chronic inflammatory disease with an autoimmune background with possible complications from peripheral (PNS) and central nervous system (CNS). The aim of this study was to assess the prevalence and to describe the phenotype of peripheral neuropathies in patients with SS. Materials & Methods We studied fifty patients with primary Sjögren's syndrome for peripheral nervous system involvement. All patients underwent neurological and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…Only one crosssectional study from China in 2018 compared pSS with sSS and reported that sSS patients had a higher prevalence of PN events than pSS patients (31.1% vs. 19%) [17]. Several previous studies found a higher frequency of symmetric sensorimotor polyneuropathy and symmetric sensory polyneuropathy [24,25], but mononeuropathy or mononeuritis multiplex was the most common pattern in these studies [21][22][23]. It is difficult to estimate the precise determination of the prevalence of these manifestations, partly due to the criteria-related variations for inclusion of patients and those related to the recruitment of patients studied, and the manifestations considered.…”
Section: Sjögren's Syndrome (Ss)mentioning
confidence: 96%
See 3 more Smart Citations
“…Only one crosssectional study from China in 2018 compared pSS with sSS and reported that sSS patients had a higher prevalence of PN events than pSS patients (31.1% vs. 19%) [17]. Several previous studies found a higher frequency of symmetric sensorimotor polyneuropathy and symmetric sensory polyneuropathy [24,25], but mononeuropathy or mononeuritis multiplex was the most common pattern in these studies [21][22][23]. It is difficult to estimate the precise determination of the prevalence of these manifestations, partly due to the criteria-related variations for inclusion of patients and those related to the recruitment of patients studied, and the manifestations considered.…”
Section: Sjögren's Syndrome (Ss)mentioning
confidence: 96%
“…SS is the second most common chronic autoimmune rheumatic disease, including primary Sjögren's syndrome (pSS) and secondary Sjögren's syndrome (sSS). We found six valid cross-sectional studies and one cohort study that discussed the prevalence and clinical features of PN in SS [17][18][19][20][21][22][23]. In the studies on pSS, the reported prevalence of PN events ranged from 19% to 72% and could be the initial manifestation [17][18][19][20][21][22][23].…”
Section: Sjögren's Syndrome (Ss)mentioning
confidence: 99%
See 2 more Smart Citations
“…Sjögren's syndrome (SS) is well-recognized as a systemic autoimmune disease, and it is characterized by manifestations of sicca (dryness) of the oral, ocular mucosa, and genital taking diverse exocrine glands as targets [ 1 ]. This disorder is categorized into primary SS existing as an independent entity and secondary SS with a coexisting entity [ 2 ]. Symptoms of secondary SS are aggravated accompanying with additional autoimmune diseases including systemic lupus erythematosus, systemic sclerosis, or rheumatoid arthritis [ 3 ].…”
Section: Introductionmentioning
confidence: 99%